Long Non-coding RNA MEG3 Promotes Renal Tubular Epithelial Cell Pyroptosis by Regulating the miR-18a-3p/GSDMD Pathway in Lipopolysaccharide-Induced Acute Kidney Injury - Deng, Junhui; Tan, Wei; Luo, Qinglin; Lin, Lirong; Zheng, Luquan; Yang, Jurong (Frontiers in Physiology, 2021)
Background and Objective: Acute kidney injury (AKI) is a complication of sepsis. Pyroptosis of gasdermin D (GSDMD)-mediated tubular epithelial cells (TECs) play important roles in pathogenesis of sepsis-associated AKI. Long noncoding RNA (lncRNA) maternally expressed gene 3 (MEG3), an imprinted gene involved in tumorigenesis, is implicated in pyroptosis occurring in multiple organs. Herein, we investigated the role and mechanisms of MEG3 in regulation of TEC pyroptosis in lipopolysaccharide (LPS)-induced AKI. Materials and Methods: Male C57BL/6 mice and primary human TECs were treated with LPS for 24 hours to establish the animal and cell models, respectively, of sepsis-induced AKI. Renal function was assessed by Periodic acid-Schiff (PAS) staining, and by evaluation of serum creatinine and urea levels. Renal pyroptosis was assessed by evaluating expression of caspase-1, GSDMD, and inflammatory factors IL-1β and IL-18. Cellular pyroptosis was assessed by analyzing the release rate of LDH, expression of IL-1β, IL-18, caspase-1, and GSDMD, and using EtBr and EthD2 staining. MEG3 expression in renal tissues and cells was detected using RT-qPCR. Bioinformatics analysis was used to screen miRNAs, and direct interaction between MEG3 and miRNAs was verified by luciferase reporter assays. Results: Pyroptosis was detected in both LPS-induced animal and cell models, and the expression of MEG3 in these models was significantly upregulated. MEG3-knockdown TECs treated with LPS showed a decreased number of pyroptotic cells, downregulated secretion of LDH, IL-1β, and IL-18, and decreased expression of GSDMD, compared with those of controls; however, there was no difference in the expression of caspase-1 between MEG3 knockdown cells and controls. Bioinformatics analysis screened out miR-18a-3P in LPS-treated TECs; miR-18a-3P expression decreased after the knockdown of MEG3, and GSDMD expression decreased after overexpression of miR-18a-3P. Dual luciferase reporter assay showed that MEG3 bound directly to miR-18a-3p, and miR-18a-3p bound directly to GSDMD. Conclusion: Our study demonstrates that lncRNA MEG3 promoted renal tubular epithelial pyroptosis by regulating the miR-18a-3p/GSDMD pathway in LPS-induced AKI.